Association of intraoperative opioid administration with postoperative pain and opioid use - Amjid Ali; Jawad Hameed; Ayesha Mairaj; Abid Haleem Khattak; Hadiqa tul Batool; Syed Faraz Bukhari (Medical Journal of South Punjab, 2024)
Objective:The primary goal of this study is to examine the impact of incentive spirometry andpeak expiratory flow meter on risks of cardiopulmonary sequelae following valve surgery. Methods:The study was conducted on36 patients operated under general anaesthesia at Lady reading hospital Peshawar. We analyzed whether the total intraoperative opioid dose predicts 30-day hospital readmission after controlling for various patient-, anaesthetist-, and case-specific factors. Results: Ambulatory surgical patients who received high intraoperative opioid doses had a substantially increased risk of readmission within 30 days after discharge. The largest adjusted risk of readmission was seen in patients receiving high doses of opioids (OR: 1.75; P <0.001). A dose–response trend was observed across quintiles (P for trend <0.05) and they also tended to return early (postoperative days 0–2 vs 3–30; P <0.001). Conclusion:High intraoperative opioid dose is a modifiable anaesthetic factor that varies in the practice of individual anaesthetists and affects postoperative outcomes. Conservative standards for intraoperative opioid dosing may reduce the risk of postoperative readmission, particularly in ambulatory surgery.